Mother and newborn survival according to point of entry and type of human resources in a maternal referral system in Kayes (Mali) - Zunzunegui Maria-Victoria; Dumont Alexandre; Fournier Pierre; Dogba Maman; Tourigny Caroline; Berthe-Cisse Safoura (BMC, 2011)
Abstract Background Since 2001, a referral system has been operating in Kayes (Mali) to reduce maternal and perinatal deaths. Normal deliveries are managed in community health centers (CHC). Complicated cases are referred to a district health center (DHC) or the regional hospital (RH). Women with obstetric emergencies can directly access the DHC and the RH. Objective To assess, in women presenting with an obstetric complication: 1) the effects of the point of entry into the referral system on joint mother-newborn survival; and 2) the effects of the configuration of healthcare team at the CHCs on joint mother-newborn survival. Method Cross-sectional study of 7,214 women users of the referral system in the region of Kayes in 2006-2009. Bivariate probit equations were fitted to estimate joint mother-newborn survival. The marginal effects of the point of entry into the referral system and of the configuration of the healthcare team at the CHCs were evaluated with a probit bivariate regression. Results Entering the referral system at the RH was associated with the best joint mother-newborn survival; the most qualified the CHCs team was, the best was mother-newborn survival. Distance traveled interacts with the point of entry and the configuration of the CHCs team. For women coming from far (over 50 km), going directly to the RH increased the probability of joint mother-newborn survival by 11.90% (p < 0.001) as compared with entry at the CHC. Entry at the CHC while coming from a distance of less than 5 km increased the likelihood of joint survival by 8.50% (p < 0.001). Among women who go first to a CHC, physician presence increased joint mother-newborn survival, compared with having no physician and fewer than three professionals. The size of the healthcare team at the CHC is significantly associated with mother-newborn survival only when distance traveled is 5 km or less. Conclusion Mother-newborn survival in the Kayes maternal referral system is influenced by combined effects of the point of care, the skill configuration of CHC personnel and distance traveled.